1999
DOI: 10.1037/0090-5550.44.3.284
|View full text |Cite
|
Sign up to set email alerts
|

George: Learning to live independently with NeuroPage®.

Abstract: The authors report the case of George, a young man with very severe memory impairments after a head injury sustained in a road traffic accident several years earlier. George was one of 200 participants in a study evaluating NeuroPage®, an electronic memory aid. Like many other participants in the study, he responded well to NeuroPage® and was able to live independently with the new memory aid. Using an ABAB single-case experimental design, the authors show his response to the pager, describe his feelings about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(23 citation statements)
references
References 8 publications
4
19
0
Order By: Relevance
“…All subjects improved their performance with the introduction of the Voice Organiser, with three subjects establishing a routine that persisted to a certain extent following the removal of the device. Similar results have been obtained by Wilson et al [57], who report that a severely memory-impaired user of NeuroPage improved on the majority of selected target behaviours such as preparing a meal. For example, beginning to prepare a meal in the evening increased from a 50% success rate before the use of the pager to a 100% success rate during pager use.…”
Section: Current Electronic Memory Aids and Usabilitysupporting
confidence: 79%
“…All subjects improved their performance with the introduction of the Voice Organiser, with three subjects establishing a routine that persisted to a certain extent following the removal of the device. Similar results have been obtained by Wilson et al [57], who report that a severely memory-impaired user of NeuroPage improved on the majority of selected target behaviours such as preparing a meal. For example, beginning to prepare a meal in the evening increased from a 50% success rate before the use of the pager to a 100% success rate during pager use.…”
Section: Current Electronic Memory Aids and Usabilitysupporting
confidence: 79%
“…After NeuroPage was withdrawn, some improvement was maintained, but this was task dependent. Similar observations in a further single-case study with NeuroPage were made by Wilson, Emslie, Quirk, and Evans (1999). Wilson et al (2001) carried out a large-scale study of 143 brain-damaged patients' use of NeuroPage.…”
Section: Electronic Communication Devicessupporting
confidence: 61%
“…Initial pilot testing with this system proved extremely successful, with all 15 patients showing a significant increase in the number of daily activities they completed with NeuroPage (Wilson, Evans, Emslie, & Malinek, 1997). Similar findings emerged in two subsequent single case studies, in which NeuroPage enabled participants to manage their medication independently and complete self-identified household chores (Evans, Emslie, & Wilson, 1998;Wilson, Emslie, Quirk, & Evans, 1999). Moreover, a larger study involving 143 participants, found that more than 80% achieved a significant improvement in the number of everyday activities they completed when using NeuroPage, with an average 30% increase in their attainment of goals (Wilson, Emslie, Quirk, & Evans, 2001).…”
Section: Compensating For Prospective Memory Deficitssupporting
confidence: 54%